Induction of hepatocyte proliferation and prevention of hepatocyte apoptosis by phenobarbital related to local humoral factor in mouse liver - He Ping; Shen Feng; Wu Meng-Chao; Li Lin-Fang; Guo Ya-Jun (Acta Pharmacologica Sinica, 2016)
AIM: To study the association of phenobarbital (Phe) inducing hepatocyte proliferation and blocking hepatocyte apoptosis with local humoral factor in liver. METHODS: The ratio of liver/body weight, DNA content, regressive rate of hyperplastic liver, and DNA fragmentation were used to investigate whether the Phe-treated mouse liver extract (PMLE) and PMLE-95 (PMLE heated at 95 degrees C for 30 min) possessed Phe-like effects on mouse liver. Meantime, the effects of pretreatment with trypsin, RNAase, and DNAase on the activity of PMLE-95 were observed, and the differences of components between PMLE-95 and NMLE-95 (normal mouse liver extract, NMLE heated at 95 degrees C for 30 min) were analyzed with HPLC. RESULTS: PMLE-95 stimulated hepatocyte proliferation and prevented hepatocyte apoptosis caused by withdrawing Phe in mice, and the activity of PMLE-95 was eliminated after the pretreatment with trypsin. On the chromatograms PMLE-95 had 5 main peaks, while NMLE-95 had only 4 peaks. CONCLUSION: The effects of Phe on the liver were mediated by an intrinsic protein or peptide substance produced in response for the stimulation of Phe in mouse liver.